Language Variation in Traditional Ritual of Dreadlock Hair Cutting in Dieng Banjarnegara: An Effort to Preserve Language and Culture - Yulia Mutmainnah (English Language and Literature International Conference (ELLiC) Proceedings, 2018)
As a multilingual country, Indonesians are accustomed to change from one language to another in one speech event. This multilingual phenomenon is also happening in Dieng Plateau of Banjarnegara Regency, Central Java. The use of more than one language is also shown in the “ruwatan” of hair cutting of dreadlocks hair that is routinely held once a year by the local community. The data of this qualitative research is taken from the interview, record and library. The results show that there are at least two languages used in the ritual, namely Javanese and Arabic. The Javanese language is used as the medium of instruction throughout the ceremonial ritual, the recitation of the mantra in the form of prayer in the Javanese language, as well as in the “tembang” sung during the ritual procession. Meanwhile, the Arabic language is used as the language of instruction in prayer readings.